PREVALENCE AND CORRELATES OF VIOLENCE AGAINST FEMALE SEX WORKERS (FSWs) IN ABUJA, NIGERIA (2011)
Violence against women (VAW) is a major public health problem affecting women globally. In addition to causing injuries and eroding women’s self esteem, violence increases the risk of reproductive health problems. However, only little is known about the magnitude and determinants of violence in female sex workers (FSWs) in Nigeria. This study assessed the prevalence and the risk factors that contribute to violence against FSWs in Abuja A descriptive cross-sectional study design was adopted. Three hundred and five brothel-based FSWs were selected using stratified random sampling and proportional allocation techniques. One hundred and ten FSWs from the high, 63 from the middle and 132 from the low income areas were interviewed using a semi-structured questionnaire. Information on occurrence of violence and predisposing factors was obtained from the respondents. In-depth interviews were conducted on 10 FSWs to obtain better insight into their recent experiences of violence. Data were analyzed using descriptive statistics, Chi-square tests and logistic regression analysis. Mean age of the respondents was 27+5.7 years. Seventy five percent had at least secondary education and majority (69.5%) were single. The prevalence of violence experienced by FSWs in the last six months was 52.8% of which 61% had been abused between once and thrice at some point in their lives. The forms of violence experienced among respondents included physical (38.7%), sexual (43.3%), psychological (32.5%) and economic (29.2%). The main perpetrators of violence were clients (47.5%), brothel managers/ owners (38.2%), local thugs (8.0%) and police men (4.0%). Bi-variate analysis showed that respondents below 30 years were less prone to physical violence than their older counterparts (P-value= 0.00). FSWs from who never attended school experienced sexual violence than those who ever attended school (p-value= 0.02). The FSWs with no formal education and those with over 10 years work experience in the sex industry were at a higher risk of psychological violence than those with formal education and with less than 10 years work experience (OR=2.6, 95% C.I= 1.37-5.08 and OR=2.3, 95%CI=1.26-4.31 respectively). Respondents with over 10 years experience in sex work were more vulnerable to economic violence than those with less than 10 years sex work experience (OR=1.9, 95%CI=1.01-3.52). Major health consequences reported were physical injury (14.1%), HIV infection (4.3%) and 10.5% reported ever had STI. Sixty percent accessed services at health facilities while 29.3% used traditional healing homes after they experienced violence. The results from the in-depth interviews showed that violence was a common experience among the respondents with clients and policemen being the main perpetrators. The prevalence of violence against FSWs in Abuja was high. Therefore, there is need to educate FSWs on their sexual rights and how to protect themselves from violence. In addition, FSWs require educational and economic empowerment to enable them move on to other more socially acceptable vocations.